The first-trimester serum high-temperature requirement protease A4 and uterine artery Doppler for the prediction of preeclampsia - Patcharaporn Siricharoenthai; Vorapong Phupong (Scientific Reports, 2023)
Abstract The objective of this study was to investigate the predictive value of serum high-temperature requirement protease A4 (HtrA4) and the first-trimester uterine artery in predicting preeclampsia in singleton pregnancy. Pregnant women at gestational age 11–13+6 weeks, who visited the antenatal clinic at King Chulalongkorn Memorial Hospital, Department of Obstetrics and Gynecology, Faculty of Medicine, Chulalongkorn University during April 2020–July 2021 were included. Serum HtrA4 levels and transabdominal uterine artery Doppler ultrasound were performed to evaluate this combination for calculating the predictive value of preeclampsia. While 371 singleton pregnant women enrolled in this study, 366 completed it. Thirty-four (9.3%) women had preeclampsia. Mean serum HtrA4 levels were higher in the preeclampsia group than in the control group (9.4 ± 3.9 vs 4.6 ± 2.2 ng/ml, p < 0.001). The mean uterine artery pulsatility index (UtA-PI) was higher in the group with early onset preeclampsia than in the control group (2.3 ± 0.5 vs 1.7 ± 0.5, p = 0.002). The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were 76.5%, 90.7%, 45.6%, and 97.4%, respectively, when using serum HtrA4 levels above 1.8 multiples of the median for the gestational age as a cut-off value for predicting preeclampsia. A combination of serum HtrA4 levels and UtA-PI > 95th percentile yielded sensitivity, specificity, PPV, and NPV of 79.4%, 86.1%, 37% and 97.6%, respectively, for the prediction of preeclampsia. A combination of serum HtrA4 levels and uterine artery Doppler in the first trimester had good sensitivity for predicting preeclampsia.